2008
DOI: 10.1038/emboj.2008.195
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 phosphorylates Cdh1 and modulates cyclin B1 stability in excitotoxicity

Abstract: Anaphase-promoting complex/cyclosome (APC/C), an E3 ubiquitin ligase that destabilizes cell cycle proteins, is activated by Cdh1 in post-mitotic neurons, where it regulates axonal growth, synaptic plasticity and survival. The APC/C-Cdh1 substrate, cyclin B1, has been found to accumulate in degenerating brain areas in Alzheimer's disease and stroke. This highlights the importance of elucidating cyclin B1 regulation by APC/C-Cdh1 in neurons under stress conditions relevant to neurological disease. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
1
19

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(179 citation statements)
references
References 46 publications
4
155
1
19
Order By: Relevance
“…The modestly shifted band of Cdh1 in the cytosol (Fig. S5E) likely reflects a hyperphosphorylatedinactive-form of Cdh1 (27). Furthermore, APC3 immunoprecipitation in the nuclear and cytosolic neuronal fractions, followed by immunoblotting against Rock1 and Rock2, revealed that the interaction between APC3 and Rock2 only occurred in the nucleus; however, no interaction between APC3 and Rock1 occurred either in the nucleus or the cytosol (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modestly shifted band of Cdh1 in the cytosol (Fig. S5E) likely reflects a hyperphosphorylatedinactive-form of Cdh1 (27). Furthermore, APC3 immunoprecipitation in the nuclear and cytosolic neuronal fractions, followed by immunoblotting against Rock1 and Rock2, revealed that the interaction between APC3 and Rock2 only occurred in the nucleus; however, no interaction between APC3 and Rock1 occurred either in the nucleus or the cytosol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we have previously described that glutamate receptor overactivation, a hallmark of neurodegenerative diseases, promotes Cdk5-induced Cdh1 phosphorylation (9,27) and inactivation, which may explain the accumulation of Rock2 that has been found in these disorders (43). Therefore, pharmacological inhibition of aberrantly accumulated Rock2 with fasudil treatment may be a suitable therapeutic strategy against these neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the changes in the activity of the proteasome, excessive NMDAR stimulation in cultured cortical neurons was also shown to induce hyperphosphorylation of the Anaphase-Promoting complex/cyclosome (APC/C) Cdh1 activator protein, which leads to a cytosolic accumulation of this E3 ligase responsible for the control of cell cycle progression (Peters, 2002;Maestre et al, 2008). The effect of excitotoxic stimulation is mediated by calpain cleavage of cyclin-dependent kinase-5 (Cdk5), with formation of a p25 product that induces the hyperphosphorylation of Cdh1 (Maestre et al, 2008). In this case, the downregulation of the E3 ligase in the nucleus allows the accumulation of cyclin B1 in this compartment, thus inducing apoptotic cell death by abnormal entry in S-phase (Almeida et al, 2005;Maestre et al, 2008).…”
Section: Ups In Glutamate-induced Excitotoxicitymentioning
confidence: 99%
“…The effect of excitotoxic stimulation is mediated by calpain cleavage of cyclin-dependent kinase-5 (Cdk5), with formation of a p25 product that induces the hyperphosphorylation of Cdh1 (Maestre et al, 2008). In this case, the downregulation of the E3 ligase in the nucleus allows the accumulation of cyclin B1 in this compartment, thus inducing apoptotic cell death by abnormal entry in S-phase (Almeida et al, 2005;Maestre et al, 2008). Excitotoxic stimulation with glutamate also downregulated total DUB activity in cultured hippocampal neurons although no effect was observed on the activity of Uch-L1, showing that not all deubiquitinating enzymes are affected (Caldeira et al, 2013).…”
Section: Ups In Glutamate-induced Excitotoxicitymentioning
confidence: 99%
“…who measured the activity of immunoprecipitates of these enzymes (46), and Sakaue et al, who tested both enzymes against several FTDP-17 mutants of tau (47). Recently, Maestras et al (48) reported that CDK5/p25 is significantly more active than CDK5/p35 toward the anaphase-promoting complex factor, cdh1, suggesting that differential enzyme activity may be substrate-dependent. Alternatively, it is possible that intracellular protein-protein, proteinlipid interactions, or posttranslational modification may differentially affect catalytic specificity in vivo.…”
Section: Discussionmentioning
confidence: 99%